Community-Based Business Technology to Improve Village Independency in Sumedang Regency - Chuzair, Andi Muhammad Yuandana Putra; Pratama, Andika Putra (Journal of Applied Business, Taxation and Economics Research, 2025)
The Desa Mandiri program, initiated by the Sumedang Regency Government, aims to enhance rural welfare and economic independence. A significant example is Cipari Village, where the Bhakti Insan Motekar (BIM) Foundation fosters agricultural entrepreneurship through community-based learning. However, sustainable agricultural development requires more than food security—it necessitates social inclusion and environmental resilience. This research proposes a Community-Based Business Technology model to support village independence, focusing on three key parameters: Technology Integration Requirements (TIR), Technological Training Methods (TTM), and Monitoring & Evaluation Mechanisms (MEM). A qualitative approach using participant observation and the Most Significant Change (MSC) method was employed to assess stakeholder perspectives, including government and foundation representatives. Findings highlight the need for technological adaptation among small-scale farmers, interactive training methodologies, and structured monitoring mechanisms. The study suggests a mobile-based technology solution as an initial step toward digital integration. Further, collaborations between government, foundations, and educational institutions can enhance capacity-building initiatives. The Koperasi model emerges as a viable framework for structuring farmer participation and monitoring progress. These findings contribute to developing scalable strategies for rural economic independence, balancing technological advancement, education, and policy support for sustainable agricultural ecosystems.